2014
DOI: 10.5709/acp-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Trait anxiety reduces affective fading for both positive and negative autobiographical memories

Abstract: The affect associated with negative events fades faster than the affect associated with positive events (the Fading Affect Bias; the FAB). The research that we report examined the relation between trait anxiety and the FAB. Study 1 assessed anxiety using the Depression, Anxiety, and Stress Scale; Studies 2 and 3 used the Beck Anxiety Inventory. Studies 1 and 2 used retrospective procedures to probe positive event memories and negative event memories while Study 3 used a diary procedure. The results of all 3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 32 publications
7
58
1
Order By: Relevance
“…However, participants who reported higher levels of depressive symptoms did not exhibit the FAB effect (i.e., the fading of affect intensity associated with positive events and negative events did not differ). Similar disruption of FAB effects has been reported for individuals who report symptoms of anxiety (Walker, Yancu, & Skowronski, ) and who endorse high levels of narcissistic traits (Ritchie, Walker, Marsh, Hart, & Skowronski, ).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…However, participants who reported higher levels of depressive symptoms did not exhibit the FAB effect (i.e., the fading of affect intensity associated with positive events and negative events did not differ). Similar disruption of FAB effects has been reported for individuals who report symptoms of anxiety (Walker, Yancu, & Skowronski, ) and who endorse high levels of narcissistic traits (Ritchie, Walker, Marsh, Hart, & Skowronski, ).…”
supporting
confidence: 68%
“…Specifically, Study 2 results revealed that even high CPA risk parents evinced a robust FAB when recalling general events. If depression or anxiety accounted for the results of Study 1, given the Walker et al () and Walker et al () results, one would have expected that high CPA risk parents would have evinced a general reduction in the FAB. This did not occur.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, in our study, the FAB for memories of events in romantic relationships was moderated by both an individual's level of sexual depression and their level of sexual self‐esteem. However, though new findings, these results closely mimic research results documenting similar alterations of the FAB in response to individual differences in general depression, anxiety, general self‐esteem, and dispositional negative mood (Ritchie et al, ; Walker et al, ; Walker, Skowronski, Gibbons, et al, ). Perhaps more novel is our finding that for those who exhibit a high need to belong, the FAB is actually reversed.…”
Section: Discussionsupporting
confidence: 85%
“…The reasoning also fits with observations indicating that the FAB is not equally evinced for all people and for all events. The FAB is diminished in individuals exhibiting dysphoria (Walker, Skowronski, Gibbons, Vogl, & Thompson, ), dispositional negative mood (Ritchie, Skowronski, Hartnett, Wells, & Walker, ), and trait anxiety (Walker, Yancu, & Skowronski, ). The FAB also varies across various properties of events, such as (a) event age (Gibbons et al, ; Ritchie et al, ; Walker et al, ), (b) whether an event is typical or atypical (Ritchie et al, ), (c) event self‐importance (Ritchie et al, ; Ritchie, Skowronski, Cadogan, & Sedikides, ), (d) whether events are psychologically open (e.g., are relevant to the current self) or are psychologically closed (e.g., are not seen as relevant to the current self; Beike & Crone, ; Beike & Wirth‐Beaumont, ; Ritchie et al, ), and (e) the vividness with which a memory is recalled (Lindeman, Zengel, & Skowronski, ; Ritchie & Batteson, ).…”
Section: The Fabmentioning
confidence: 99%